Antibacterial effect of linezolid against methicillin-resistant Staphylococcus aureus evaluated using colorimetry and chemiluminescence-based drug-susceptibility tests - Hiramatsu, Keiichi; Tajima, Yutaka; Yamashiro, Yuichiro; Komatsu, Mitsutaka; Ito, Teruyo (Japanese Journal of Chemotherapy, 2006)
The number of methicillin-resistant Staphylococcus aureus (MRSA) clinical isolates with reduced susceptibility to vancomycin (VCM) has been increasing, necessitating the development of measures against infections caused by such strains. We evaluated the antibacterial activity of a new agent, linezolid (LZD), in MRSA strains with varying VCM susceptibility. To do so, we used 3 methods-microbroth dilution to determine minimal growth inhibitory concentrations (MICs), chemiluminescence-based drug susceptibility testing, and the alamaBlue ® reaction measuring bacterial metabolic activity. MICs of LZD ranged from 0.5μg/mL to 3μg/mL and did not correlate with those of VCM, which ranged from 0.5μg/mL to 8μg/mL. Chemiluminescence assay showed that LZD significantly reduced chemiluminescence intensity linked to bacterial metabolic activity. As the LZD concentration increased, intensity decreased steeply, indicating that LZD strongly suppress bacterial metabolism in short incubation. Although time-kill assays showed that LZD is bacteriostatic, alamaBlue ® reactions reflecting bacterial metabolic activity showed that LZD had a suppression time curve similar to VCM. This data suggests that the initial time required for LZD to affect bacterial cells was nearly equal to that for VCM.Our data suggests that LZD has a strong antibacterial activity against MRSA strains, including VRSA, and that this drug is a promising new antibiotic for treating MRSA infections.